Comparative analysis of leadership training concepts in high schools in the UK and Ukraine - Romanovskyi, O. G.; Gura, Tetyana; Chala, Yuliia; Knysh, A. Ye. (НТУ "ХПІ", 2016)
The paper presents a consistent comparative analysis of the leadership training concepts in the United Kingdom and Ukraine, based on the example of the University of Greenwich and the National Technical University "Kharkiv Polytechnic Institute". We define basic principles of leadership training at the Department of pedagogy and psychology of social systems management. Special attention is paid to the importance of implementing a synergetic approach in the training of modern managers-leaders. The highlighted similarities in leadership training in the UK and Ukraine are the synergistic approach, cluster approach, a focus on the personal traits development of future leaders.

В статті представлено послідовний порівняльний аналіз концепцій підготовки лідерів в Сполученому Королівстві та Україні, на прикладі Університету Грінвіча та Національного технічного університету "Харківський політехнічний інститут". Визначено основні принципи підготовки лідерів на кафедрі педагогіки і психології управління соціальними системами. Окрема увага приділена важливості реалізації синергетичного підходу при підготовці сучасних управлінців-лідерів. Виділені спільні риси підготовки лідерів у Великобританії та Україні: синергетичний підхід, кластер ний підхід, орієнтація на розвиток особистісних якостей майбутніх лідерів.
Порівняльний аналіз концепцій підготовки лідерів в вищих навчальних закладах Великобританії та України
Keywords: leadership concept; leadership training; humanitarian and technical elite; synergistic approach; cluster approach; лідерство; концепція підготовки лідерів; гуманітарно-технічна еліта; синергетичний підхід; кластерний підхід